Pengaruh Kompetensi dan Motivasi Terhadap Kinerja Pegawai pada Institut Agama Islam Negeri Kerinci - Yogi Ahmad Yani (Journal of Islamic Economics and Bussiness Studies, 2022)
This study aims to determine the effect of competence and motivation on employee performance at the Kerinci State Islamic Institute (IAIN). The data used in this study is primary data with a sample of 49 people. The data analysis technique used is multiple linear regression. The results of the study show that competence has a significant effect on employee performance, this is evidenced by t count > t table (2.982 > 2.021), motivation has a significant effect on employee performance, this is evidenced by t count > t table ((-2.145) > (-2.021)) . Competence and motivation simultaneously have a significant effect on employee performance, this is evidenced by F count > F table (8.733 > 2.81). The magnitude of the influence of Competence and Motivation on Employee Performance at IAIN Kerinci simultaneously is 27.5% and the remaining 72.5% is influenced by other variables that were not examined in this study.